The soldier's guide the complete guide to U.S. Army traditions, training, duties, and responsibilities (Skyhorse Publishing, 2016)
A comprehensive guide for the ultimate guardians of American freedom-the U.S. soldier. The Soldier's Guide applies to every soldier in the Army#x97;active, reserve, and National Guard#x97;in every rank and specialty. It condenses important information from a number of U.S. Army regulations, field manuals, and other publications into one crucial volume. This manual describes the soldier's role in the Army and the soldier's obligations. Other subject areas are Army history, training, and professional development. This manual also describes standards in appearance and conduct and selected individual combat tasks that are important for every soldier to master.